Eksplorasi Sejarah Pemikiran Hukum: Integrasi Filsafat Hukum dan Sosiologi Hukum pada Perppu Nomor 2 Tahun 2017 tentang Organisasi Kemasyarakatan - Rohman, Saipul; Mulyono; Singalodra, Nurita; Ayudya Maharani, Dinar (UNES Law Review, 2024)
Government Regulation in Lieu of Law (Perppu) No. 2/2017 on Mass Organizations was issued by President Joko Widodo on 10 July 2017. This Perppu amends several provisions in Law Number 17 of 2013 concerning Community Organizations, in response to the activities of mass organizations that are considered to threaten national unity and national security. In this research, the theoretical framework used is Lawrence M. Friedman's Legal Culture Theory, which emphasizes the substance, structure, and culture of law. This Perppu reflects the influence of cultural and historical factors in its formation, with efforts to create social justice through the regulation of mass organizations. The integration of legal philosophy, legal sociology, and historical approaches in the juridical analysis of this Perppu results in a holistic and in-depth perspective, essential for effective and equitable implementation in society. This research argues that the integration of these approaches helps to develop legal policies that are more just, contextual, and responsive to social change, and avoid potential abuse of power.